USM ATHLETE EXCELS IN SEA GAMES SAILING EVENT - MPRC, Pusat Media & Perhubungan Awam (USM, 2015)
PENANG, June 2015 – A Universiti Sains Malaysia (USM) athlete, Geh Cheow Lin, 20, has made the country proud by winning two silver medals in the sailing event at the recently concluded 28 SEA Games held at the Singapore National Sailing Centre.